2016
DOI: 10.1007/s00464-016-4937-3
|View full text |Cite
|
Sign up to set email alerts
|

Laser visual guidance versus two-dimensional vision in laparoscopy: a randomized trial

Abstract: BackgroundDuring laparoscopy, the surgeon’s loss of depth perception and spatial orientation is problematic. Laser visual guidance (LVG) is an innovative technology that improves depth perception to enhance the visual field. In this trial, we examined the effect of LVG on surgical novices’ motor skills, quality of task performance, and cognitive workload.MethodsWe designed a randomized controlled trial following the CONSORT statement. Thirty-two surgical novices completed the Training and Assessment of Basic L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In general, studies presenting a higher MERSQI score were those that used an RCT design. The main characteristics of all included studies, as well as the MERSQI score for each are shown in Table S2 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…In general, studies presenting a higher MERSQI score were those that used an RCT design. The main characteristics of all included studies, as well as the MERSQI score for each are shown in Table S2 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating technologies like the MLD into traditional C-arm education can assist novice operators in achieving efficient and accurate imaging [ 11 ]. The visual guidance provides real-time feedback to facilitate spatial conceptualization and minimize trial-and-error adjustments [ 12 , 13 ]. This enhances learning efficiency while reducing risks associated with excessive radiation and surgical complications [Wu, 2023 #3298].…”
Section: Discussionmentioning
confidence: 99%
“…This allows the laser projections to visualize the underlying X-ray trajectories on the body surface. By enabling users to align the laser with the target position on the screen, the MLD provides visual guidance for rapid and accurate positioning [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation